Camel viral diseases: Current diagnostic, therapeutic, and preventive strategies - Kandeel, Mahmoud; Al-Mubarak, Abdullah I. A. (Frontiers in Veterinary Science, 2022)
Many pathogenic viruses infect camels, generally regarded as especially hardy livestock because of their ability to thrive in harsh, arid conditions. Transmission of these viruses has been facilitated by the commercialization of camel milk and meat and their byproducts, and vaccines are needed to prevent viruses from spreading. There is a paucity of information on the effectiveness of viral immunizations in camels, even though numerous studies have looked into the topic. More research is needed to create effective vaccines and treatments for camels. Because Camels are carriers of coronavirus, capable of producing a powerful immune response to recurrent coronavirus infections. As a result, camels may be a suitable model for viral vaccine trials since vaccines are simple to create and can prevent viral infection transfer from animals to humans. In this review, we present available data on the diagnostic, therapeutic, and preventative strategies for the following viral diseases in camels, most of which result in significant economic loss: camelpox, Rift Valley fever, peste des petits ruminants, bovine viral diarrhea, bluetongue, rotavirus, Middle East respiratory syndrome, and COVID-19. Although suitable vaccines have been developed for controlling viral infections and perhaps interrupting the transmission of the virus from the affected animals to blood-feeding vectors, there is a paucity of information on the effectiveness of viral immunizations in camels and more research is needed. Recent therapeutic trials that include specific antivirals or supportive care have helped manage viral infections.